Particular Chromosomal Distribution of Microsatellites in Five Species of the Genus Gymnotus (Teleostei, Gymnotiformes) - Utsunomia, Ricardo [UNESP]; Melo, Silvana [UNESP]; Scacchetti, Priscilla Cardim [UNESP]; Oliveira, Claudio [UNESP]; Machado, Milla de Andrade; Pieczarka, Julio Cesar; Nagamachi, Cleusa Yoshiko; Foresti, Fausto [UNESP] (Mary Ann Liebert, Inc, 2018)
Microsatellites show great abundance in eukaryotic genomes, although distinct chromosomal distribution patterns might be observed, from small dispersed signals to strong clustered motifs. In Neotropical fishes, the chromosome mapping of distinct microsatellites was employed several times to uncover the origin and evolution of sex and supernumerary chromosomes, whereas a detailed comparative analysis considering different motifs at the chromosomal level is scarce. Here, we report the chromosomal location of several simple sequence repeats (SSRs) in distinct electric knife fishes showing variable diploid chromosome numbers to unveil the structural organization of several microsatellite motifs in distinct Gymnotus species. Our results showed that some SSRs are scattered throughout the genomes, whereas others are particularly clustered displaying intense genomic compartmentalization. Interestingly, the motifs CA, GA, and GAG exhibited a band-like pattern of hybridization, useful for the identification of homologous chromosomes. Finally, the colocalization of SSRs with multigene families is probably related to the association of microsatellites with gene spacers in this case.
Keywords: cytogenetics; neotropical fish; repetitive DNA; SSR; genome compartmentalization